Nano modified polyethylene optical cable sheath material and preparation method thereof

By adding modified nylon fibers and composite flame retardants to the optical cable sheath material, the oxidative corrosion and fire safety issues of optical cables in humid environments are solved, and the mechanical and flame retardant properties of the material are improved to ensure stable signal transmission and safety.

CN119241937AActive Publication Date: 2025-01-03JIANGSU DUOMEISH OPTOELECTRONIC COMMUNICATIONS CO LTD

Patent Information

Application Number
CN202411465732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Existing optical cable sheath materials are prone to oxidation and corrosion in humid environments, and polyvinyl chloride materials release toxic gases during fires. Polyethylene materials are flammable, resulting in signal distortion and safety threats, and it is necessary to improve the mechanical and flame retardant properties of the materials.

Method used

By adding modified nylon fibers and composite flame retardant, dopamine was modified with molybdenum disulfide surface and grafted nanosilica to enhance polyamide 6 fibers, and grafted benzene with magnesium-aluminum dihydroxide as the core and maleic anhydride Ethylene-ethylene-butadiene-styrene block copolymer is a composite flame retardant of the shell, which improves the mechanical and flame retardant properties of the material.

Benefits of technology

The tensile strength, impact strength and flame retardant properties of the material are significantly improved, ensuring that the optical cables can transmit signals stably in humid environments and prevent the release of toxic gases in the event of fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of optical cable material preparation, and discloses a nano-modified polyethylene optical cable sheath material and a preparation method thereof.The nano-modified polyethylene optical cable sheath material is prepared from, by weight, 80-100 parts of high-density polyethylene, 25-40 parts of EVA resin, 10-15 parts of modified nylon fibers, 5-8 parts of a composite flame retardant, 0.1-1 part of an antioxidant, 0.1-2 parts of a coupling agent and 0.5-5 parts of a lubricant; the modified nylon fiber is a modified molybdenum disulfide reinforced polyamide 6 fiber, and the modified molybdenum disulfide is formed by grafting nano silicon dioxide after modifying dopamine on the surface of molybdenum disulfide; the composite flame retardant is a core-shell flame retardant which takes magnesium-aluminum double hydroxide as a core and a maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as a shell, and a P-N flame retardant is distributed in the core shell. The polyethylene optical cable sheath material is endowed with good mechanical property and flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical cable material preparation, and specifically relates to a nano-modified polyethylene optical cable sheath material and a preparation method thereof. Background Art

[0002] In recent years, the communication industry has developed rapidly, and the demand for optical cables has gradually increased. However, communication optical cables are usually in a humid environment, which can easily cause oxidation and corrosion of the metal belt protective layer and distortion of the optical fiber signal. In order to improve the reliability and service life of the optical fiber signal, the upper and lower surfaces of the metal belt are usually heated and bonded with hot melt adhesive to form a metal-plastic composite belt for armoring and shielding, and protected with an outer protective layer (sheath material).

[0003] The sheath material as the outer protective layer of the optical cable has an important impact on the service life of the optical cable and the metal-plastic shielding layer. The optical cable has different requirements for the performance of the protective layer due to different installation locations. For optical fiber cables laid underground or in pipelines, the sheath is required to have excellent mechanical properties and be easy to install to meet the normal transmission of optical fiber signals. For optical fibers and overhead optical cables installed indoors in high-rise buildings, they must not only have good mechanical properties, but also be fire-retardant. Therefore, optical cable manufacturers and users should fully study and understand the functions and process differences of different sheath materials.

[0004] Polyethylene (PE) and polyvinyl chloride (PVC) are the most widely used in flame-retardant optical cable sheath materials. Among them, PVC is cheap and easy to process. It is mostly used in fireproof insulation and sheath flame-retardant materials for overhead optical cables. However, when PVC sheath materials burn in natural fires, they will release toxic gases and thick smoke, endangering health and safety. Polyethylene (PE) has developed rapidly in communication optical fiber cable insulation and sheath materials due to its good chemical stability, non-toxicity, low dielectric loss and high dielectric strength. However, PE is flammable. When a fire occurs, optical fiber cables installed indoors will cause secondary fires, posing a threat to people's lives and property. In addition, its incompatibility with inorganic fillers has limited its application. Therefore, improving the compatibility of inorganic flame retardants with organic matrices and enhancing the strength of cable materials are necessary prerequisites for the development of high-performance PE-based cable sheath materials. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a nano-modified polyethylene cable sheath material and a preparation method thereof, and to give the material good mechanical properties and flame retardant properties by adding modified nylon fiber and composite flame retardant.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 80-100 parts of high-density polyethylene, 25-40 parts of EVA resin, 10-15 parts of modified nylon fiber, 5-8 parts of composite flame retardant, 0.1-1 parts of antioxidant, 0.1-2 parts of coupling agent, and 0.5-5 parts of lubricant; The modified nylon fiber is a modified molybdenum disulfide reinforced polyamide 6 fiber, and the modified molybdenum disulfide is molybdenum disulfide surface modified with dopamine and then grafted with nano-silicon dioxide; The composite flame retardant is a core-shell flame retardant with magnesium aluminum double hydroxide as a core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as a shell, and PN flame retardant distributed in the core-shell.

[0007] Further preferably, the method for preparing the modified nylon fiber comprises the following steps: (1) Dissolve tris(hydroxymethyl)aminomethane in deionized water, add 0.1 mol / L hydrochloric acid to adjust the pH to 8-9, then add dopamine hydrochloride to the above solution and stir to mix evenly, then add molybdenum disulfide powder, stir to mix, ultrasonically treat for 2-4 hours, and react at 60°C for 24 hours, centrifuge, wash, filter and dry the product to obtain polydopamine-modified molybdenum disulfide; (2) adding nano-silica powder to a mixture of anhydrous ethanol and deionized water in a volume ratio of 10:1, stirring evenly and then ultrasonically dispersing for 1 to 2 hours to obtain a nano-silica dispersion, then adding 3-aminopropyltrimethoxysilane to the dispersion, stirring and heating to 80°C for reaction for 3 to 5 hours, centrifugally washing, filtering and drying to obtain silane-modified nano-silica; (3) adding polydopamine-modified molybdenum disulfide to N,N-dimethylformamide and ultrasonically treating it for 20 to 40 minutes to form a uniform suspension, then adding the silane-modified nano-silica obtained in step S2 to the above suspension, ultrasonically treating it again for 20 to 40 minutes, and then heating it to 100 to 110° C., stirring and reacting for 4 to 6 hours, centrifuging, washing, filtering and drying the product to obtain the modified molybdenum disulfide; (4) The modified nylon fibers were prepared by a one-step process on a high-speed spinning machine by blending the nylon fibers with polyamide 6 chips in proportion, with the melting and spinning temperatures being 260-280 °C, the draft ratio being 1.25, and the winding speed being 4500 m / min.

[0008] Further preferably, in step (1), the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:10-15.

[0009] Further preferably, in step (2), the mass ratio of the nano-silica powder to 3-aminopropyltrimethoxysilane is 12-15:1.

[0010] Further preferably, in step (3), the mass ratio of polydopamine-modified molybdenum disulfide to silane-modified nano-silicon dioxide is 3-5:1.

[0011] Further preferably, the preparation method of the composite flame retardant comprises the following steps: A. Dissolve magnesium nitrate powder and aluminum nitrate powder in deionized water, add 1.5 mol / L sodium hydroxide solution and stir rapidly until a white precipitate is produced, and then react at room temperature for 1 hour, then add toluene to the solution, ultrasonicate for 1 hour, then add concentrated hydrochloric acid and 3-aminopropyltriethoxysilane, ultrasonicate for 1 hour, transfer to a water bath, react at 90°C for 24 hours, cool to room temperature, ultrasonicate with ethanol for three times, filter, and dry at 60°C for 16-20 hours to obtain magnesium aluminum layered double hydroxide; B. Dissolve PEG in anhydrous ethanol at a mass ratio of 1:5 to obtain a PEG ethanol solution, then mix the magnesium aluminum layered double hydroxide powder and the PEG ethanol solution for 20 to 30 minutes, filter, wash, and dry to obtain a PEG-treated magnesium aluminum layered double hydroxide; C. Put maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer into an open mill for melting, add PEG-treated magnesium aluminum layered double hydroxide, ammonium polyphosphate, pentaerythritol and melamine, and melt mix at 185-195° C. for 5-10 minutes to obtain the core-shell flame retardant.

[0012] Further preferably, the molar ratio of magnesium nitrate to aluminum nitrate in step A is 2:1.

[0013] Further preferably, in step B, the solid-to-liquid ratio of the magnesium aluminum layered double hydroxide powder to the PEG ethanol solution is 1:5-8.

[0014] Further preferably, in step C, the mass ratio of maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer, PEG-treated magnesium aluminum layered double hydroxide, ammonium polyphosphate, pentaerythritol and melamine is 4:1:0.5:0.2:0.2.

[0015] A method for preparing a nano-modified polyethylene optical cable sheath material comprises the following steps: S1. Add high-density polyethylene, EVA resin, antioxidant, coupling agent and lubricant into a high mixing pot and mix them thoroughly for 10-20 minutes. Then, melt, plasticize and blend the mixture through a twin-screw extruder, and extrude and granulate to obtain polymer particles. S2. Add the polymer particles, modified nylon fibers and composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying.

[0016] Beneficial effects of the present invention: The present invention modifies the surface of molybdenum disulfide with dopamine and then grafts nano-silicon dioxide, and then strengthens polyamide 6 by modified molybdenum disulfide to obtain modified nylon fiber, thereby improving the strength and wear resistance of nylon fiber. When added to polyethylene material, the tensile strength and impact resistance of the material can be significantly improved. The composite flame retardant of the present invention adopts maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer to coat magnesium aluminum double hydroxide to form a core-shell structure, thereby improving the dispersion effect of inorganic flame retardant in polymer matrix, and at the same time, PN flame retardant is doped in the maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer shell by blending, which can cooperate with inorganic flame retardant to promote each other in flame retardancy, and can give the material good flame retardant performance. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] It should be noted that all the raw materials used in this embodiment are commercially available reagents, among which the antioxidant is one or more of antioxidant 300, antioxidant 168, and antioxidant 1010, the coupling agent is one or more of silane coupling agent KH550, silane coupling agent KH560, silane coupling agent Si-69, titanate coupling agent NDZ-201, and titanate coupling agent JTW-311, and the lubricant is one or more of stearate, paraffin, and polyethylene wax. Example

[0019] A method for preparing modified nylon fiber comprises the following steps: (1) Dissolve 6.0 g of tris(hydroxymethyl)aminomethane in 50 ml of deionized water, add 0.1 mol / L hydrochloric acid to adjust the pH to 8-9, then add 2.5 g of dopamine hydrochloride to the above solution and stir to mix evenly, then add 30.5 g of molybdenum disulfide powder, stir to mix, then ultrasonically treat for 3 h, and react at 60 ° C for 24 h, centrifuge, wash, filter and dry the product to obtain polydopamine-modified molybdenum disulfide; (2) Add 7.5 g of nano-silica powder to a mixture of 50 ml of anhydrous ethanol and deionized water in a volume ratio of 10:1, stir evenly and disperse by ultrasonic for 1.5 h to obtain a nano-silica dispersion, then add 0.5 g of 3-aminopropyltrimethoxysilane to the dispersion, stir and heat to 80°C for 4 h, centrifuge, wash, filter and dry to obtain silane-modified nano-silica; (3) 4.0 g of polydopamine-modified molybdenum disulfide was added to 50 ml of N,N-dimethylformamide and ultrasonically treated for 20 to 40 min to form a uniform suspension, and then 1.2 g of the silane-modified nano-silica obtained in step S2 was added to the above suspension, and ultrasonically treated again for 30 min, and then heated to 105° C. and stirred for reaction for 5 h. The product was centrifuged, washed, filtered and dried to obtain the modified molybdenum disulfide; (4) The modified nylon fibers were prepared by a one-step process on a high-speed spinning machine by blending the nylon fibers with polyamide 6 chips in proportion, with the melting and spinning temperatures being 260-280 °C, the draft ratio being 1.25, and the winding speed being 4500 m / min. Example

[0020] A method for preparing a composite flame retardant comprises the following steps: A. Dissolve 10.5g magnesium nitrate powder and 5.3g aluminum nitrate powder in 80ml deionized water, add 50ml 1.5mol / L sodium hydroxide solution and stir rapidly until a white precipitate is produced, and then react at room temperature for 1h, then add toluene to the solution, ultrasonicate for 1h, then add 5ml concentrated hydrochloric acid and 2.5g 3-aminopropyltriethoxysilane, ultrasonicate for 1h, transfer to a water bath, react at 90°C for 24h, cool to room temperature, ultrasonicate with ethanol three times, filter, and dry at 60°C for 18h to obtain magnesium aluminum layered double hydroxide; B. Dissolve PEG in anhydrous ethanol at a mass ratio of 1:5 to obtain a PEG ethanol solution, then mix 4.5 g of magnesium aluminum layered double hydroxide powder and 30 ml of the PEG ethanol solution for 20-30 min, filter, wash, and dry to obtain a PEG-treated magnesium aluminum layered double hydroxide; C. 40 g of maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer was melted in an open mill, and 10 g of PEG-treated magnesium aluminum layered double hydroxide, 5 g of ammonium polyphosphate, 2 g of pentaerythritol, and 2 g of melamine were added, and melt-mixed at 190° C. for 8 min to obtain the core-shell flame retardant. Example

[0021] A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 80 parts of high-density polyethylene, 40 parts of EVA resin, 10 parts of modified nylon fiber, 8 parts of composite flame retardant, 0.1 parts of antioxidant 1010, 0.05 parts of silane coupling agent KH5500, 0.05 parts of titanate coupling agent NDZ-201, and 5 parts of stearate; The modified nylon fiber is the modified molybdenum disulfide reinforced polyamide 6 fiber prepared in Example 1; the composite flame retardant is the core-shell flame retardant prepared in Example 2, which has magnesium aluminum double hydroxide as the core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as the shell, and PN flame retardant distributed in the core-shell.

[0022] The preparation method of the nano-modified polyethylene optical cable sheath material comprises the following steps: S1, adding high-density polyethylene, EVA resin, antioxidant 1010, silane coupling agent KH550, titanate coupling agent NDZ-201, and stearate into a high mixing pot and mixing them thoroughly for 15 minutes, then melting, plasticizing, and blending the mixture through a twin-screw extruder, and extruding and granulating to obtain polymer particles; S2. Add the polymer particles, modified nylon fibers and composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying. Example

[0023] A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 100 parts of high-density polyethylene, 25 parts of EVA resin, 15 parts of modified nylon fiber, 5 parts of composite flame retardant, 1 part of antioxidant 300, 1 part of silane coupling agent KH560, 1 part of titanate coupling agent JTW-311, and 0.5 part of paraffin; The modified nylon fiber is the modified molybdenum disulfide reinforced polyamide 6 fiber prepared in Example 1; the composite flame retardant is the core-shell flame retardant prepared in Example 2, which has magnesium aluminum double hydroxide as the core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as the shell, and PN flame retardant distributed in the core-shell.

[0024] The preparation method of the nano-modified polyethylene optical cable sheath material comprises the following steps: S1. Add high-density polyethylene, EVA resin, antioxidant 300, silane coupling agent KH560, titanate coupling agent JTW-311 and paraffin into a high mixing pot and mix them thoroughly for 10 minutes. Then, melt, plasticize and blend the mixture through a twin-screw extruder, and extrude and granulate to obtain polymer particles. S2. Add the polymer particles, modified nylon fibers and composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying. Example

[0025] A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 90 parts of high-density polyethylene, 32 parts of EVA resin, 13 parts of modified nylon fiber, 6 parts of composite flame retardant, 0.5 parts of antioxidant 168, 0.5 parts of silane coupling agent KH550, 0.5 parts of silane coupling agent Si-69, and 3 parts of polyethylene wax; The modified nylon fiber is the modified molybdenum disulfide reinforced polyamide 6 fiber prepared in Example 1; the composite flame retardant is the core-shell flame retardant prepared in Example 2, which has magnesium aluminum double hydroxide as the core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as the shell, and PN flame retardant distributed in the core-shell.

[0026] The preparation method of the nano-modified polyethylene optical cable sheath material comprises the following steps: S1, adding high-density polyethylene, EVA resin, antioxidant 168, silane coupling agent KH550, silane coupling agent Si-69, and polyethylene wax into a high mixing pot and mixing them thoroughly for min, then melting, plasticizing, and blending the mixture through a twin-screw extruder, and extruding and granulating to obtain polymer particles; S2. Add the polymer particles, modified nylon fibers and composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying.

[0027] Comparative Example 1 A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 90 parts of high-density polyethylene, 32 parts of EVA resin, 6 parts of composite flame retardant, 0.5 parts of antioxidant 168, 0.5 parts of silane coupling agent KH550, 0.5 parts of silane coupling agent Si-69, and 3 parts of polyethylene wax; The composite flame retardant is a core-shell flame retardant prepared in Example 2, which has magnesium aluminum double hydroxide as a core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as a shell, and PN flame retardant distributed in the core-shell.

[0028] The preparation method of the nano-modified polyethylene optical cable sheath material comprises the following steps: S1, adding high-density polyethylene, EVA resin, antioxidant 168, silane coupling agent KH550, silane coupling agent Si-69, and polyethylene wax into a high mixing pot and mixing them thoroughly for min, then melting, plasticizing, and blending the mixture through a twin-screw extruder, and extruding and granulating to obtain polymer particles; S2. Add the polymer particles and the composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying.

[0029] Comparative Example 2 A nano-modified polyethylene optical cable sheath material comprises the following raw materials in parts by weight: 90 parts of high-density polyethylene, 32 parts of EVA resin, 13 parts of modified nylon fiber, 0.5 parts of antioxidant 168, 0.5 parts of silane coupling agent KH550, 0.5 parts of silane coupling agent Si-69, and 3 parts of polyethylene wax; The modified nylon fiber is the modified molybdenum disulfide reinforced polyamide 6 fiber prepared in Example 1.

[0030] The preparation method of the nano-modified polyethylene optical cable sheath material comprises the following steps: S1, adding high-density polyethylene, EVA resin, antioxidant 168, silane coupling agent KH550, silane coupling agent Si-69, and polyethylene wax into a high mixing pot and mixing them thoroughly for min, then melting, plasticizing, and blending the mixture through a twin-screw extruder, and extruding and granulating to obtain polymer particles; S2. Add the polymer particles and the modified nylon fibers into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying.

[0031] Performance Testing 1. Mechanical properties test The nano-modified polyethylene cable sheath materials in Examples 3 to 5 and Comparative Examples 1 to 2 were cut into test specimens, and mechanical properties were tested using a universal testing machine. Referring to GB / T 528-2009, the molded specimens were cut into 25 mm × 4 mm dumbbell-shaped tensile specimens, and the tensile rate was 20 mm / min. The test results are shown in Table 2: Table 1 Test results of mechanical properties of nano-modified polyethylene cable sheath material

[0032] It can be seen from the data in Table 1 that the mechanical properties of the material prepared in Comparative Example 1 are worse than those of other groups. The present invention modifies the surface of molybdenum disulfide with dopamine and then grafts nano-silicon dioxide, and then strengthens polyamide 6 by modified molybdenum disulfide to obtain modified nylon fiber, thereby improving the strength and wear resistance of the nylon fiber. Adding it to polyethylene material can significantly improve the tensile strength and impact strength of the material.

[0033] 2. Flame retardant performance test The nano-modified polyethylene cable sheath materials in Examples 3 to 5 and Comparative Examples 1 to 2 were made into standard specimens of 127×12.7×3.2 mm, and horizontal and vertical (UL-94) burning tests were performed according to ASTM D3801-1996 standard. At the same time, an oxygen index test (LOI) was performed according to ASTM D2863-70 standard, and the data obtained are shown in Table 2 below.

[0034] Table 2 Test results of flame retardant properties of nano-modified polyethylene optical cable sheath material

[0035] It can be seen from the data in Table 2 that the flame retardant performance of the cable sheath layer material prepared in Comparative Example 2 is worse than that of other groups. No composite flame retardant is added in Comparative Example 3. The composite flame retardant of the present invention adopts maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer to coat magnesium aluminum double hydroxide to form a core-shell structure, which improves the dispersion effect of the inorganic flame retardant in the polymer matrix. At the same time, the PN flame retardant is doped in the maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer shell by blending, which can synergistically promote the flame retardancy with the inorganic flame retardant, and can give the material good flame retardant performance.

[0036] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A nano-modified polyethylene optical cable sheath material, characterized in that: The invention comprises the following raw materials in parts by weight: 80 to 100 parts of high-density polyethylene, 25 to 40 parts of EVA resin, 10 to 15 parts of modified nylon fiber, 5 to 8 parts of composite flame retardant, 0.1 to 1 part of antioxidant, 0.1 to 2 parts of coupling agent and 0.5 to 5 parts of lubricant; The modified nylon fiber is a modified molybdenum disulfide reinforced polyamide 6 fiber, and the modified molybdenum disulfide is molybdenum disulfide surface modified with dopamine and then grafted with nano-silicon dioxide; The composite flame retardant is a core-shell flame retardant with magnesium aluminum double hydroxide as a core, maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer as a shell, and PN flame retardant distributed in the core-shell.

2. The nano-modified polyethylene optical cable sheath material according to claim 1, characterized in that: The preparation method of the modified nylon fiber comprises the following steps: (1) dissolving tris(hydroxymethyl)aminomethane in deionized water, adding 0.1 mol / L hydrochloric acid to adjust the pH to 8-9, then adding dopamine hydrochloride to the above solution and stirring and mixing evenly, then adding molybdenum disulfide powder, stirring and mixing, ultrasonically treating for 2-4 hours, and reacting at 60° C. for 24 hours, centrifuging, washing, filtering and drying the product to obtain polydopamine-modified molybdenum disulfide; (2) adding nano-silica powder to a mixture of anhydrous ethanol and deionized water in a volume ratio of 10:1, stirring evenly and then ultrasonically dispersing for 1 to 2 hours to obtain a nano-silica dispersion, then adding 3-aminopropyltrimethoxysilane to the dispersion, stirring and heating to 80° C. for reaction for 3 to 5 hours, centrifugally washing, filtering and drying to obtain silane-modified nano-silica; (3) adding polydopamine-modified molybdenum disulfide to N,N-dimethylformamide and ultrasonically treating it for 20 to 40 minutes to form a uniform suspension, then adding the silane-modified nano-silicon dioxide obtained in step S2 to the above suspension, ultrasonically treating it again for 20 to 40 minutes, then heating it to 100 to 110° C., stirring and reacting for 4 to 6 hours, centrifuging, washing, filtering and drying the product to obtain the modified molybdenum disulfide; (4) The modified nylon fibers were prepared by a one-step process on a high-speed spinning machine by blending the nylon fibers with polyamide 6 chips in proportion, with the melting and spinning temperatures being 260-280°C, the draft ratio being 1.25, and the winding speed being 4500 m / min.

3. The nano-modified polyethylene optical cable sheath material according to claim 2, characterized in that: In the step (1), the mass ratio of dopamine hydrochloride to molybdenum disulfide is 1:10-15.

4. The nano-modified polyethylene optical cable sheath material according to claim 2, characterized in that: In the step (2), the mass ratio of the nano-silicon dioxide powder to 3-aminopropyltrimethoxysilane is 12 to 15:

1.

5. The nano-modified polyethylene optical cable sheath material according to claim 2, characterized in that: In the step (3), the mass ratio of polydopamine-modified molybdenum disulfide to silane-modified nano-silicon dioxide is 3 to 5:

1.

6. The nano-modified polyethylene optical cable sheath material according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: A. Dissolve magnesium nitrate powder and aluminum nitrate powder in deionized water, add 1.5 mol / L sodium hydroxide solution and stir rapidly until a white precipitate is produced, and then react at room temperature for 1 hour, then add toluene to the solution, ultrasonicate for 1 hour, then add concentrated hydrochloric acid and 3-aminopropyltriethoxysilane, ultrasonicate for 1 hour, transfer to a water bath, react at 90°C for 24 hours, cool to room temperature, ultrasonicate with ethanol for three times, filter, and dry at 60°C for 16-20 hours to obtain magnesium aluminum layered double hydroxide; B. dissolving PEG in anhydrous ethanol at a mass ratio of 1:5 to obtain a PEG ethanol solution, then mixing the magnesium aluminum layered double hydroxide powder and the PEG ethanol solution for 20 to 30 minutes, filtering, washing, and drying to obtain a PEG-treated magnesium aluminum layered double hydroxide; C. Put maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer into an open mill for melting, add PEG-treated magnesium aluminum layered double hydroxide, ammonium polyphosphate, pentaerythritol and melamine, and melt mix at 185-195° C. for 5-10 minutes to obtain the core-shell flame retardant.

7. The nano-modified polyethylene optical cable sheath material according to claim 6, characterized in that: The molar ratio of magnesium nitrate to aluminum nitrate in step A is 2:

1.

8. The nano-modified polyethylene optical cable sheath material according to claim 6, characterized in that: In the step B, the solid-to-liquid ratio of the magnesium aluminum layered double hydroxide powder to the PEG ethanol solution is 1:5-8.

9. The nano-modified polyethylene optical cable sheath material according to claim 6, characterized in that: In the step C, the mass ratio of maleic anhydride grafted styrene-ethylene-butadiene-styrene block copolymer, PEG-treated magnesium aluminum layered double hydroxide, ammonium polyphosphate, pentaerythritol and melamine is 4:1:0.5:0.2:0.

2.

10. A method for preparing the nano-modified polyethylene optical cable sheath material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add high-density polyethylene, EVA resin, antioxidant, coupling agent and lubricant into a high-mixing pot and mix them thoroughly for 10 to 20 minutes. Then, melt, plasticize and blend the mixture through a twin-screw extruder, and extrude and granulate to obtain polymer particles. S2. Add the polymer particles, modified nylon fibers and composite flame retardant into a high mixing pot for premixing, then melt and blend the mixture through a twin-screw extruder, extrude and granulate the mixture, and obtain the nano-modified polyethylene optical cable sheath material after drying.

Citation Information

Patent Citations

  • Oil-resistant high-flame-retardant cable material as well as preparation method and application thereof

    CN112538200A

  • High-performance optical cable thermoplastic sheath material and preparation method thereof

    CN114874532A

  • Wear-resistant fluororubber composite material and preparation method thereof

    CN117402445A

Cited By

  • Novel modified flame-retardant polyethylene material

    CN120040902A

  • A new type of modified flame-retardant polyethylene material

    CN120040902B

  • High-strength directly-buried optical cable and preparation method thereof

    CN120507849A

  • A high-strength direct-buried optical cable and its preparation method

    CN120507849B